“Not Entirely on His Side”: The Assumption of Sexed Subjectivity in Alice Munro’s “Boys and Girls” - Jennifer MURRAY (E-REA)
The enigma of sexual difference is the nodal point of Alice Munro’s “Boys and Girls” (1968). The Lacanian concept of sexuation, which defines the positions of ‘man’ and ‘woman’ as belonging to discordant logical structures, will serve to illuminate the complex path of the unnamed female protagonist of this short story (and secondarily, of her younger brother) in coming to assume a position as a sexed subject. While the oedipal structure, including Lacan’s revision of Freud’s account, clarifies the initial identifications and idealizations which inform the process of sexuation, the story brings to light the inadequacy of this perspective to situate the speaking being as ‘sexed’. Through a metaphorical parallel with the fate of the farm horses, Mack and Flora, each of the children will encounter, incarnated in the figure of the father, the law of the symbolic order, or in other words, the necessity of symbolic castration; each will be called upon to assume a position on the side of man, or of woman.